Development of 3D patient-based super-resolution digital breast phantoms using machine learning. (13th November 2018) - Caballo, Marco; Fedon, Christian; Brombal, Luca; Mann, Ritse; Longo, Renata; Sechopoulos, Ioannis
Abstract: Digital phantoms are important tools for optimization and evaluation of x-ray imaging systems, and should ideally reflect the 3D structure of human anatomy and its potential variability. In addition, they need to include a good level of detail at a high enough spatial resolution to accurately model the continuous nature of the human anatomy. A pipeline to increase the spatial resolution of patient-based digital breast phantoms that can be used for computer simulations of breast imaging is proposed. Given a tomographic breast image of finite resolution, the proposed methods can generate a phantom and increase its resolution at will, not only simply through super-sampling, but also by generating additional random glandular details to account for glandular edges and strands to compensate for those that may have not been detected in the original image due to the limited spatial resolution of the imaging system used. The proposed algorithms use supervised learning to predict the loss in glandularity due to limited resolution, and then to realistically recover this loss by learning the mapping between low and high resolution images. They were trained on high-resolution synchrotron images (detector pixel size 60 μ m) reconstructed at seven voxel dimensions (60 μ m–480 μ m), and applied to patient images acquired with a clinical breast CT system (detector pixel size 194 μ m) to generate super-resolution phantoms (voxel sizes 68 μ m). Several evaluations were made to assess the appropriateness of the developed methods, both with the synchrotron (relative prediction error 0.010  ±  0.004, recovering accuracy 0.95  ±  0.04), and with the clinical images (average glandularity error at 194 μ m: 0.15%  ±  0.12%). Finally, a breast radiologist assessed the realism of the developed phantoms by blindly comparing original and phantom images, resulting in not being able to distinguish the real from the phantom images. In conclusion, the proposed method can generate super-resolution phantoms from tomographic breast patient images that can be used for future computer simulations for optimization of new breast imaging technologies.